Production of gamma-valerolactone from furfural by a single-step process using Sn-Al-Beta zeolites: Optimizing the catalyst acid properties and process conditions - Winoto, Haryo Pandu; Ahn, Byoung Sung; Jae, Jungho (ELSEVIER SCIENCE INC, 2016)
A bifunctional Sn-Al-Beta zeolite which possesses isolated Lewis and Bronsted acid sites was prepared by a post-synthesis procedure and applied to the one-pot conversion of furfural to gamma-valerolactone (GVL), a value-added chemical. Sn-Al-Beta was capable of catalyzing a cascade of the transfer hydrogenation and hydrolysis of furfural to GVL by the interplay of Lewis and Bronsted acid sites. The degree of dealumination and the tin-incorporation method largely influence the acid properties of the catalyst and the catalyst selectivity. A high yield of GVL up to 60% was obtained with Sn-Al-Beta 7 (Si/Sn = 63 and Si/Al = 473) at 180 degrees C in 2-butanol. (C) 2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: MEERWEIN-PONNDORF-VERLEY; BAEYER-VILLIGER OXIDATIONS; LEVULINIC ACID; CELLULOSIC SUGARS; SILICA-ALUMINA; SITES; CONVERSION; ISOMERIZATION; REDUCTION; BIOMASS